A LIBRARY RESEARCH: THE IMPLEMENTATION OF GENRE BASED APPROACH IN INDONESIAN VOCATIONAL HIGH SCHOOLS - Astuti, Sari; Afrianni, Luthfia; Cahyani, Indah Fathyyah (JOLADU: Journal of Language Education, 2022)
Genre Based Approach (GBA) had been implemented for a decade in English Curriculumof Indonesia. It was expected that this approach could develop four  language skills simultaneously through its four stages of teaching and learning cycles, namely Building Knowlege of Field (BKOF), Modelling of Text (MOT), Join Construction of Text (JCOT) and Independent Construction of Text (ICOT). This study aims to review the implementation of GBA in Vocatioanal High School (VHS) and its impact to the learning process. It applied a library research to analyze two thesis and six research journals on the implementation GBA in VHS that focus mostly in writing skills. The results show that teachers  have applied GBA using the correct stages though there are some weaknesses within the process. Teachers and students give positive response toward the implementation of GBA that can be seen through their  enthusiam during  the teaching  and learning process. Finally, this study also revealed that GBA can improve students learning results that is proven from the students’writing scores that increase after the implementation of GBA.